Amino acid sequence requirements in the human IgAI hinge for cleavage by streptococcal IgAI proteases. (August 2002) - Senior, B. W.; Batten, M. R.; Kilian, M.; Woof, J. M.
Abstract : All the IgA1 proteases of the different pathogenic species of Streptococcus cleave the hinge of the α chain of human IgA1 only at one proline-threonine peptide bond. In order to study the importance of these amino acids for cleavage, several hinge mutant recombinant IgA1 antibodies were constructed. The mutations were found to be without major effect upon the structure or functional abilities of the antibodies. However, they had a major effect upon their sensitivity to cleavage by some of the IgA1 proteases.